Analysis of the Concept of Tawarruq in the Perspective of Sharia Economic Law - Naerul Edwin Kiky Aprianto; Iftiarini Rahmatun Nazilah (el-Uqud: Jurnal Kajian Hukum Ekonomi Syariah, 2023)
Tawarruq is one of the sharia transaction schemes that can be used as an alternative for parties needing cash urgently. The scheme is a way for related parties to avoid usury activities. In Sharia financing, this contract was developed by ulema to adapt to society's sociological and economic development over time. The results of this study are manifested in Islamic financing agreements. Bai' al-inah and tawarruq are two types of financing in sharia economic law. However, tawarruq seems to be still in the debate whether it is allowed or prohibited, while bai' al-inah is forbidden because of the nash hadith which forbids it. In traditional societies, this scheme is applied between individuals, whereas today it has begun to be applied in Islamic financial institutions, especially abroad. One of the obstacles faced in implementing this scheme is the lack of public understanding due to the limited literature on this scheme, especially the literature in Indonesian.